Good Governance, Transparency, and Accountability in Regional Financial Management: A Literature Review - Rizaldi Setiawan; Muhammad Riban Satia (International Journal Labs, 2026)
Local Public Financial Management is a key issue in public sector economics, as it relates to the effective use of public resources and local government performance. Numerous studies have examined the role of good governance, transparency, and accountability in local public financial management; however, their findings remain fragmented and inconsistent. This article aims to synthesize the literature on the mechanisms through which good governance improves local government financial performance. Using a library research approach, this study analyzes 20 accredited national journal articles and 12 reputable international journal articles published between 2015 and 2025. The findings indicate that good governance does not directly affect financial performance but operates through transparency and accountability as mediating mechanisms. Moreover, the digitalization of public financial management strengthens transparency, although its impact on accountability and performance is conditional. This article aims to synthesize national and international literature on good governance mechanisms in improving the financial performance of local governments from the economic perspective of the public sector.